«Our experience has become our university and sociology was accreted by it...» - Rotman, David G.; Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2019)
The interview is dedicated to the upcoming 75th anniversary of the famous Belarusian sociologist, director of the Centre of Sociological and Political Studies of the Belarusian State University, doctor of science (sociology), full professor David G. Rotman. He reflects on his life path, the role of sociology in society, research projects, his teachers and colleagues, and the problems which researchers face. The conversation touches on the topics: of methodology and methods of sociology; interdisciplinarity, comparability, conjunction and combination of methods are considered as basic requirements for contemporary research. The issues of the Belarusian sociology perspective directions and improving the sociological education is discussed.